Hubungan Usia Ibu dan Ketuban Pecah Dini dengan Kejadian Persalinan Prematur di Rumah Sakit AS Kabupaten Kediri Tahun 2022 - Nurul Mulkil Aliyah; Rahajeng Siti Nur Rahmawati; Sumy Dwi Antono; Susanti Pratamaningtyas (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Introduction: The highest infant mortality rate (IMR) is caused by premature birth. Premature birth can occur spontaneously or through cesarean section that occurs between 20 weeks of gestation and <37 weeks. This study was conducted with the aim of determining the relationship between maternal age and premature rupture of membranes with the incidence of preterm labor. Method: Correlational study (relationship) using a case-control method. Simple random sampling technique was used to select a sample of 118 respondents from a population of 166 mothers who gave birth prematurely at AS Hospital, Kediri Regency in January - December 2022. Patient medical records were used as a source of data collection. Analysis of this study using the Exact Fisher Test correlation test. Results: The relationship between maternal age and the incidence of premature labor was not found to have a significant relationship with the result of 0.725 > 0.05. While the relationship between premature rupture of membranes and preterm labor was found to have a significant relationship with the result of 0.008 < 0.05. Conclusion: There is no significant relationship between maternal age <20 / > 35 years and 20-35 years with premature birth and there is a significant relationship between premature rupture of membranes (KPD) and premature birth at AS Hospital, Kediri Regency in 2022